Knowledge Management Implementation Readiness Assessment: Case Study of PT PELNI (Persero) - Mia Agustina; Dana Indra Sensuse (Budapest International Research and Critics University, 2022)
This study aims to identify Knowledge Management (KM) implementation factors, highlight KM implementation elements, and assess PT PELNI (Persero)'s readiness for KM implementation. The investigation employs the Analytical Hierarchy Process (AHP) and Likert Summated Ratings (LSR) techniques. For readiness evaluation respondents, there were 23 respondents who served as human capital staff. According to the findings of this study, PT PELNI (Persero) has eight factors with a total of 38 indicators. Furthermore, the factor related such as Top Management Factor, Executive Management Factor, Culture Factor, Organizational Infrastructure Factor, Human Resource Management Factor, Continuous Improvement Factor KM Architecture Factor, Technical Infrastructure Factor are listed in order based on their relative significance. By then, based on the level of readiness, the results of the overall evaluation of readiness are unprepared. On the other hand, based on the results of the respondent's summary, the majority of the indicators are considered ready for implementation. This signifies that employee are prepared to adopt the KM program, but the KM team believes that there is room for development in each KM implementation indication before the program can be implemented.